2020
DOI: 10.1111/aos.14562
|View full text |Cite
|
Sign up to set email alerts
|

Myopia prevalence in Denmark – a review of 140 years of myopia research

Abstract: Purpose To evaluate potential changes in myopia prevalence in Denmark by revising more than 100 years of myopia research. Methods A systematic literature search was performed in the PubMed, Embase and Cochrane Library databases. Only studies reporting a myopia prevalence in Denmark were included. Myopia was defined using the definition in individual references. We did not restrict inclusion of studies to specific methods of measuring or evaluating refraction. As refraction changes throughout life, information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
5
19
0
Order By: Relevance
“… 40 A recent review found no evidence of an increase in myopia prevalence in Denmark over a 140-year period, which runs counter to the increasing prevalence in Asian countries. 41 …”
Section: Discussionmentioning
confidence: 99%
“… 40 A recent review found no evidence of an increase in myopia prevalence in Denmark over a 140-year period, which runs counter to the increasing prevalence in Asian countries. 41 …”
Section: Discussionmentioning
confidence: 99%
“… 58 Neither in Denmark, where nearly 140 years of myopia research did not find a convincing change in prevalence of myopia. 92 Asian ancestry does not inevitably lead to myopia, since the prevalence of myopia in these areas was much lower two or three generations ago. 88 , 93 This suggests that environmental and social factors must be involved in the promotion of myopia in modern populations.…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of myopia in Danish children aged 4.5-7 years ranged from 0.0% in year 2015-2016 to 8.9% in schoolchildren aged 7-10 years in year 1882. The same study showed that the prevalence of myopia was 7.2% in Danish children aged 10-14 years in year 1961-1962 and was 24.0% among children aged 11-14 years in year 1882 1 . In contrast with our findings, in East Asian countries the cumulative incidence of myopia ranges between 33.6% and 54% 10 , and the annual incidence rate of myopia varies from 30 cases per 100-person years 11 to 31.7 cases per 100-person years 12 .…”
Section: Discussionmentioning
confidence: 86%
“…A study from Denmark compared the myopia prevalence in 29 Danish studies between the years 1882 and 2018 and found no evidence of an increase in myopia numbers over the years 1 . The prevalence of myopia in Danish children aged 4.5-7 years ranged from 0.0% in year 2015-2016 to 8.9% in schoolchildren aged 7-10 years in year 1882.…”
Section: Discussionmentioning
confidence: 99%